Fabricating a Sustainable Roller Compacted Concrete Containing Recycled Waste Demolished Materials: A Literature Review - Alaa S. Shamran; Zena K. Abbas (Journal of Engineering, 2024)
The key benefits connected with Roller-Compacted Concrete Pavement (RCCP) technology are costs reduction of life-cycle, shrinkage decrease, opening to traffic at an earlier time, and a cooling of the city's core are. This technology received much consideration recently for applications in highway tenders. Several attempts worked on instill sustainable implementation in RCCP using alternate materials. This work presented a thorough review of the literature on alternative materials for RCCP published between 1997 and 2021. Recycled concrete and asphalt pavement aggregates are two examples of alternative materials to traditional quarry rock that have been studied. Critical evaluations of the mechanical properties of RCCP have been used to assess these alternative aggregates' potential. This article explains how the basic properties for the materials impact the RCCP's behavior. The results of a comprehensive study into utilizing the substitute aggregates in manufacturing RCCPs showed the best mix ratios for attaining long-term sustainability. Along with identifying potential future study topics. This research additionally indicates several knowledge gaps that can only be filled by further research and experimentation.